The infection characteristics and autophagy defect of dermal macrophages in STZ‐induced diabetic rats skin wound Staphylococcus aureus infection model - Xiaoying Xie; Rihui Zhong; Ling Luo; Xianghua Lin; Lisi Huang; Songyin Huang; Lijia Ni; Baiji Chen; Rui Shen; Li Yan; Chaohui Duan (Immunity, Inflammation and Disease)
Abstract Introduction Diabetic foot ulcer infection (DFI) is an infectious disease of the skin and soft tissue in diabetics notorious for making rapid progress and being hard to cure. Staphylococcus aureus (S. aureus), most frequently detected in DFI, recently was suggested as an intracellular pathogen that can invade and survive within mammalian host cells. Autophagy in macrophages plays a vital immune role in combating intracellular pathogens through bacterial destruction, but there is a lack of empirical research about the infection characteristics and autophagy in diabetic skin infection. Methods Here, we used streptozotocin‐induced Sprague Dawley rats as a diabetic skin wound model to examine the S. aureus clearance ability and wound healing in vitro. Western blot and immunofluorescence staining were used to evaluate the autophagic flux of the macrophages in diabetic rats dermis, even with S. aureus infection. Results We demonstrated that infections in diabetic rats appeared more severe and more invasive with weakened pathogen clearance ability of the host immune system, which coincided with the suppressed autophagic flux in dermal macrophages, featured by a significant increase in endogenous LC3II/I and in p62. Conclusions Our results first provided convincing evidence that autophagy of macrophages was dysfunctional in diabetes, especially after being infected by S. aureus, which weakens the intracellular killing of S. aureus, potentially worsens the infections, and accelerates the infection spread in the diabetic rat model. Further understanding of the special immune crosstalk between diabetes host and S. aureus infection through autophagic factors will help to explain the complex clinical phenomenon and guarantee the development of effective therapies for diabetic foot infections.